Role of Intense Pulse Light Therapy on Dry Eyes in Pakistani Population - Sameen, Murtaza; Shahid, Muhammad; Adnan, Muhammad; Rauf, Abdul; Ahmad, Jawwad; Naimat, Khalid (Pakistan Armed Forces Medical Journal, 2024)
Objective: To observe the role of Intense Pulse Light therapy on dry eyes in Pakistani population.Study Design: Analytical cross-sectional study.Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi Pakistan, from Feb to Dec 2022.Methodology: A total of 88 patients with meibomian gland related dry eyes were included in this study, with age ranging between 25-65 years. Intense pulsed light therapy was used to treat Meibomian Gland Dysfunction related dry eyes. Tear film break up time before and after the sessions was recorded on a data collection tool and data analysis was done.Results: Out of 88 patients with Meibomian Gland Dysfunction related dry eyes, 60(68.2%) were females and 28(31.8%) were males. Mean age of the patients was 45.5±8.0 years and median tear film break up time (per Intense Pulse Light) was 4(5–3) seconds, whereas median tear film break-up time (post Intense Pulse Light) was increased to 12(13–11) seconds. Follow up was done until 4 months, which showed significant improvement in symptoms of patients. Tear Breakup Time did not improve in 2 patients as they were already on anti-glaucoma treatment (p-value